Ayurveda Medicinal Plant Bala (Sida Cordifolia Linn.) from Vedas, Samhitas and Nighantus: A Literary Review (AYUSHDHARA, 2021)
Background: Sida cordifolia (Linn.) commonly known as Bala, belonging to a family malvaceae is a very important medicinal plant since long in a traditional remedy of India. The drug is given many vernacular names i.e. Kharethi in Hindi, Baladana in Gujarati and Chikana in Malayalam etc. Medicinal plant Bala review is very helpful to achieve Ayurveda literature. Data Source: The information has been collected from many research articles, Vedas, Samhitas and Nighanus and internet sources etc. to the concept of medicinal uses of Bala. Conclusion: Bala in different Vedas and Samhitas we find it’s different to indicate Vishaghna, Brihmana, Kantikarka, Grahi, Vrishya, Ojhovardhaka, Balya, Rasayan properties and in all Nighantus its Madhura Rasa, Snigdha Guna, Shita Virya, Madhura Vipaka have been mentioned excluding Raja Nighantu which have not indication its Guna and Virya. Various types of Bala are clear by Samahitas and Nighantus under groups of Baladvaya, Balatraya, Balachatushtaya and Balapanchaya. The review displays that Bala is used in many disorders like Vatarakta, Jwara, Vyanga, Vata-Vyadhi and Nilika etc. in Samhitas it is used in different forms of drug i.e. Basti, Peya, Shaka, Yavagu, Ghrita, Taila, Pralepa, Kashaya, Sweda and Lepa etc. and many synonyms are presents various Nighantus. This study review highlights its description in Vedas, Samhitas and Nighantus.